Isolation and structural studies of oligostilbenes from vatica sp. / Wan Zuraida Wan Mohd Zain … [et al.] - Wan Mohd Zain, Wan Zuraida; Latip, Jalifah; Daud, Shaari; Mat So'ad, Siti Zaiton (Research Management Institute (RMI), 2010)
Isolation compound and biological activity have been done on stem bark of Vatica odorata which collected at Mata Kail, Hutan Belum, Perak and Vatica bella from Jengka, Pahang. All samples were extracted with acetone and methanol at room temperature to give VOKM (methanol extract of Vatica odorata); VOKA(acetone extract of Vatica odorata); VBKM(methanol extract of Vatica Bella) and VBKA(acetone extract of Vatica Bella). The extracts were further subjected to purification by using several chromatographic techniques such as thin layer chromatography, vacuum liquid chromatography and radial thin layer chromatography. Two known compounds namely (-)-a-viniferin and (+)-vaticanol B were isolated from this two plant samples, while a known compound namely e-viniferin were isolated from V bella and (-)-hopeafenol were isolated from V odorata. All isolated compounds were elucidated by using their physical properties (physical form, melting point, optical rotation) and several spectroscopic methods such as infrared spectrophotometry (IR), ultraviolet-visible (UV-VTS), mass spectroscopy (MS) and nuclear magnetic resonance spectroscopy (NMR) and also by comparison with the literature data…